Comparison of the Minimum Inhibitory and Mutant Prevention Drug Concentrations for Pradofloxacin and 7 Other Antimicrobial Agents Tested Against Swine Isolates of Actinobacillus pleuropneumoniae and Pasteurella multocida - Joseph M. Blondeau; Shantelle D. Fitch (Molecules)
Pradofloxacin is a dual targeting, bactericidal fluoroquinolone recently approved for treating bacteria causing swine respiratory disease. Currently, an abundance of in vitro data does not exist for pradofloxacin. We determined the minimum inhibitory concentration (MIC) and mutant prevention concentrations (MPC) of pradofloxacin compared to ceftiofur, enrofloxacin, florfenicol, marbofloxacin, tildipirosin, tilmicosin and tulathromycin against swine isolates of Actinobacillus pleuropneumoniae and Pasteurella multocida. Overall, pradofloxacin had the lowest MIC and MPC values as compared to the other agents tested. For example, pradofloxacin MIC values for 50%, 90% and 100% of A. pleuropneumoniae strains were ≤0.016 µg/mL, ≤0.016 µg/mL and ≤0.016 µg/mL and for P. multocida were ≤0.016 µg/mL, ≤0.016 µg/mL and 0.031 µg/mL, respectively. The MPC values for 50%, 90% and 100% of A. pleuropneumoniae strains were 0.031 µg/mL, 0.063 µg/mL and 0.125 µg/mL and for P. multocida were ≤0.016 µg/mL, 0.031 µg/mL and 0.0.063 µg/mL, respectively. By MPC testing, all strains were at or below the susceptibility breakpoint. Based on MPC testing, pradofloxacin appears to have a low likelihood for resistance selection. This study represents the most comprehensive in vitro comparison of the above noted drugs and the first report for pradofloxacin and tildipirosin.